2018
DOI: 10.1158/1541-7786.mcr-18-0284
|View full text |Cite|
|
Sign up to set email alerts
|

Circular RNA ciRS-7 Maintains Metastatic Phenotypes as a ceRNA of miR-1299 to Target MMPs

Abstract: Circular RNA ciRS-7 has been reported to act as a competing endogenous RNA (ceRNA) of the miRNA miR-7, resulting in reduced miR-7 activity and increased miR-7-targeted transcripts. However, it is unknown if ciRS-7 harbors other miRNAs with regulatory roles in triple-negative breast cancer (TNBC). The present study determined that the expression of ciRS-7 in TNBC clinical specimens and representative cells is significantly higher than other breast cancer subtypes. Functionally, downregulation of ciRS-7 inhibite… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
63
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 79 publications
(65 citation statements)
references
References 34 publications
2
63
0
Order By: Relevance
“…Our finding was similar to previous studies, circRNA ciRS-7 could act as the ceRNA of miR-1299 to promote migration and invasion of triple-negative breast cancer cells. 30 Taken together, circ_0006528 might regulate the resistance of breast cancer cells to PTX by binding to miR-1299.…”
Section: Discussionmentioning
confidence: 99%
“…Our finding was similar to previous studies, circRNA ciRS-7 could act as the ceRNA of miR-1299 to promote migration and invasion of triple-negative breast cancer cells. 30 Taken together, circ_0006528 might regulate the resistance of breast cancer cells to PTX by binding to miR-1299.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that circular RNAs play a central regulatory role in the pathogenesis of a variety of cancer types (7,8). Studies have also verified that circular RNAs, as competitive endogenous RNAs, bind to miRNAs and regulate the expression of downstream target genes (9)(10)(11). For example, circular RNA circNASP has been shown to regulate OS malignant behavior via the miR-1253/FOXF1 axis (12).…”
Section: Introductionmentioning
confidence: 98%
“…CircRNAs can regulate target gene expression by interacting with corresponding microRNAs (miRNAs) (Zhang et al, 2015). CircRNAs can function as miRNA "sponges" and regulate gene transcription (Hansen et al, 2013;Sang et al, 2018). For example, circRNA-ITCH increases ITCH gene expression by acting as an miRNA sponge by interacting with miR-7, miR-17, and miR-214.…”
Section: Introductionmentioning
confidence: 99%